2015
DOI: 10.1016/j.ejbas.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of glycyrrhizin and omega-3 fatty acids on Nuclear Factor-kappa B pathway in thioacetamide-induced fibrosis in rats

Abstract: Available online xxx Keywords:Liver fibrosis Glycyrrhizin Omega-3 fatty acids NF-kB MDA a b s t r a c t Nuclear Factor kappa B (NF-kB) is a key transcriptional regulator that plays important roles in the pathogenesis of hepatic inflammation and fibrosis in chronic liver diseases.NF-kB activation leads to production of pro-inflammatory and fibrogenic cytokines.Glycyrrhizin (GL) is reported to suppress liver fibrosis and cirrhosis. Omega-3 fatty acids (u-3) play an anti-inflammatory role and they are reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…The histopathological alterations were confined to both hepatic cells and portal areas that showed moderate to great thickening by mononuclear cells infiltration and biliary epithelial hyperplasia and then progressed by the time giving more severe lesions at ten weeks post to involve bridging necrosis as well as markedly thickened and extended portal area giving the nodular appearance. Similar results were documented by Abo El-Magd et al (2015) and Osman (2016). Moreover, TAA intoxication disturbs lipid metabolism as our data revealed a significant elevation in serum TG and TC with a significant reduction in HDL in TAA-treated rats in addition to hepatocytic vacuolation of fatty type that were found at the ten weeks of the treatment (Mustafa et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…The histopathological alterations were confined to both hepatic cells and portal areas that showed moderate to great thickening by mononuclear cells infiltration and biliary epithelial hyperplasia and then progressed by the time giving more severe lesions at ten weeks post to involve bridging necrosis as well as markedly thickened and extended portal area giving the nodular appearance. Similar results were documented by Abo El-Magd et al (2015) and Osman (2016). Moreover, TAA intoxication disturbs lipid metabolism as our data revealed a significant elevation in serum TG and TC with a significant reduction in HDL in TAA-treated rats in addition to hepatocytic vacuolation of fatty type that were found at the ten weeks of the treatment (Mustafa et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, TAA intoxication caused intense oxidative stress as evidenced by the dramatic increase in the hepatic MDA concentration. This was in consistence with a previous study [16,21]. Oxidative stress is believed to be a major participating factor in TAA-induced liver fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…In most cases, the improvement in bilirubin concentration was rapid and reached a normal level, whereas ALP concentration was not significantly decreased during the first 4 weeks after initiating therapy with omegaven [19], regarding STB and ALP, this agrees with the results of our study. Analysis of our data showed that administration of OMG-3 fish oil to alcohol-fed rats resulted in a significant increase in serum TP and ALB levels, these findings were in agreement with [41] who studied hepatoprotective activity of omega-3 fish oil against thioacetamide-induced fibrosis in rats. In addition [42], demonstrated that the increase in concentration of serum TP and ALB within the normal range in rabbits fed on economic control diet supplemented with 0.5 and 1.0 mL fish oil per day/kg live bodyweight may reflect an increase in the hepatic function when animals were fed on fish oil.…”
Section: Effects Of Gte and Omega-3 On Liver Injury Biomarkerssupporting
confidence: 92%